KEPEMIMPINAN STRATEGIS DALAM KOPERASI: UPAYA MENDORONG KEPUTUSAN BERBASIS DATA DAN PROFESIONALISME PENGELOLAAN - Nabilatus Sholihah; Nurul Maharani; Vaudi Windi Aulia (PT. Hasba Edukasi Mandiri, 2026)
Cooperatives in Indonesia continue to face fundamental challenges in leadership quality and data-driven decision-making capacity. This article aims to examine comprehensively how strategic leadership—encompassing cooperative entrepreneurship orientation, managerial competence, and adaptive capability—can promote professionalism in cooperative management. The study employs a literature review approach, analyzing ten scientific journals published between 2021 and 2025. Findings indicate that effective leadership styles, both transformational and servant, produce tangible impacts on organizational performance and member satisfaction. Data-driven decision-making—through instruments such as the Balanced Scorecard, decision support systems, and financial statement analysis—has been shown to enhance management objectivity. Conversely, weak human resource capacity among administrators, poor governance, and limited training remain persistent structural barriers. This article concludes that transforming cooperative leadership requires a holistic approach that integrates cooperative values with modern managerial skills, including data literacy and information technology.